Liberal Thought in Qurâanic Studies: Tracing Humanistic Approach to Sacred Text in Islamic Scholarship - Setiawan, M. Nur Kholis (Al-Jamiah Research Centre, 2007)
Literary approach to the Quran developed by al-Khuli created deep critiques from its opponents, in whose opinion, the usage of literary paradigm to the study of the Qurâan, according to them, implied a consequence of treating the Qurâan as a human text which clearly indicates a strong influence of a liberal mode of thinking that goes out of the line of the Qurâanâs spirit. This article shows a diametric fact compared to that they have claimed. The data proves that linguistic aspects of the Qurâan have succeeded in making an intellectual connection among progressive and liberal scholars in the classical and modern era. This supports the assumption that progressive and liberal thought whose one of its indicators is freedom of thought in accordance to Charles Kurzman term, is âchildrenâ of the Islamic civilization. Freedom of thought in the classical Islamic scholarship should be the Ã©lan of intellectualism including the field of Quranic studies.